RESPIRATORY DISTRESS: A RARE PRESENTATION OF RICKETS - Siddiqui, Tahir Saeed (Journal of Ayub Medical College Abbottabad, 2006)
Nutritional rickets has multiple presentations like skeletal deformities, tetany, hypocalcemic seizures, recurrent diarrhea, dental abnormalities, developmental delay and floppiness. Here a rare presentation of nutritional rickets is reported in five months old baby who had respiratory distress since two months and signs of respiratory distress resolved after start of vitamin-D supplementation. Keywords: Nutritional Rickets, Respiratory Distress, Vitamin D